E-Fa (education First Aid) Game Sebagai Upaya Peningkatan Layperson Penanganan Cedera Anak Usia Sekolah: Development and Usability Study - Eky Madyaning Nastiti; Rida Darotin (NHM PRESS, 2022)
Background: The prevalence of injuries in first-year school-aged children has increased due to unsafe conditions and a low understanding of the concept of danger and first aid Purpose: developed the “E-Fa (Education First Aid) Game as an education for handling injuries to school-age children in junior high school Method: This study uses a quantitative approach to the application of E-Fa (Education First Aid) involving 50 junior high school students in Jember Regency. This application was developed in two stages, the first stage was the development of a game-based application called E-Fa (Education First Aid). The second stage is an expert test involving emergency nurses, nursing lecturers with specialization in emergency departments and information systems experts. Results: Based on the reliability evaluator value test using Intraclass correlation, it shows a value of 0,964, meaning that the developed application has an adequate reliability coefficient. the feasibility test on 50 respondents stated that 86,76% of the applications were declared very feasible. Conclusion: The development of the E-Fa Game application through a game-based Smartphone as an injury management education is very appropriate to be used as an effort to increase the Layperson for handling injuries to school-age children.